Gender differences in myocardial infarction: health professionals’ point of view - Foà, Chiara; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2016)
Backgroud and aims: Aim of this study is contributing to an analysis of healthcare professionals’ perceptions of gender differences in myocardial infarction. Method: For this purpose, the study examines bio-clinical and psychosocial aspects of myocardial infarction in men and women, thanks to 8 focus groups attended by healthcare professionals working at Milan Hospital (Niguarda Ca’ Granda), Parma University Hospital, Catania Hospital (Ospedale Cannizzaro) and Ancona INRCA (Scientific Institute recognized in the area of Geriatrics and Gerontology). Results: A qualitative analysis of the narratives have been aggregated in 5 code families: “pathophysiological peculiarities”, “psycho-relational peculiarities”, “therapeutic problems”, “protection and risk factors”, and “no difference” between men and women, in particular as far as diagnostic-therapeutic treatment is concerned. Pathophysiological peculiarities concern the acknowledgement of typically female characteristics which can affect clinical pathways, such as comorbidity and different symptoms. Psycho-relational peculiarities show women’s attitudes toward symptoms underestimation and a high pain endurance. Therapeutic problems are connected to female physio-pathological peculiarities, which reduce treatment effectiveness. Protection and risk factors indicate peculiar protective conditions or potentially dangerous situations in female population, such as distress and greater responsibilities. Conclusions: The study confirms the “male model” of heart disease and a gap in evaluating and dealing with female infarction. The study takes into account differences in narratives,